STATE OF DEVELOPMENT OF THE HOSPITALITY INDUSTRY IN THE NUR-SULTAN CITY - Mizambekova Zh.K.; Zhakupov A.A.; Zhumanazarov K.B.; Toloubay M.; Tulegenova K.T. (Academic Journal of Physical and Chemical Sciences, 2020)
In this paper an assessment of the state of the hospitality industry of Nur Sultan city is given. The authors note that there is a positive dynamics of the increase in the hotel room inventory in the industry in the period under review, at the same time they note that there is a low degree of workload in accommodation facilities for guests of the capital of Kazakhstan in comparison with the capitals of other countries. The analysis of the subjects of the hospitality industry of the city by the indicators of their number, the distribution of their belonging to the category were carried out. It was revealed that in the structure of the accommodated guests, Kazakhstanis coming from other regions are dominated. At the same time, the analysis shows a gradual increase in the share of foreign tourists in the overall structure of accommodated guests in hotel facilities. As a constraint to the development of the hospitality industry in the capital the unfair competition in the market has been marked, due to the presence of the daily rent apartments illegally handed by individuals. First of all, this circumstance makes it difficult to conduct a real assessment of the market size of the hospitality industry in Nur-Sultan city, secondly, deprives guest accommodation of potential customers due to lower prices for illegal daily rent of apartments. In addition, the results of the analysis of the pricing policy of the capital’s accommodation facilities show the inadequacy of pricing for their services.